Application of analytical hierarchical process in assessing the suitability of land for growing grain crops - Olsid Mema; Etleva Jojic; Perparim Laze; Mykyta Khramov; Oleksandr Lymar (Наукові горизонти)
Assessing the suitability of land for growing grain crops is a relevant issue for ensuring sustainable agricultural production and improving food security. The Analytical Hierarchy Process (AHP) is an effective method of multi-criteria evaluation that systematically addresses all parameters. The study aimed to analyse the usage of the AHP method to determine the weight and priorities of different soil and climate characteristics to analyse the suitability of land for cereal crop cultivation, using wheat as an example. The study identified key factors affecting yields and developed recommendations for effective land management. An AHP was employed to weight various criteria, including physical, chemical and climatic characteristics. The data were processed to determine the impact of each factor on land suitability, with consistency checks to ensure the reliability of the results. The study showed that Flood and erozion hazard characteristics (32.2%) and Soil pysichal characteristics (25.6%) are the most important physical factors. Acidity (pH) and Cation Exchange Capacity (CEC) have a significant impact on nutrient availability, while average temperature and precipitation determine the main climatic conditions for wheat growth. Flood and erosion risks are also addressed for the long-term suitability assessment. The AHP was used to assess the suitability of land for wheat cultivation, identifying the most important factors and their weights. Practical recommendations included applying agronomic measures to reduce erosion risks and improve soil fertility. The results of the study can be used by agronomists, land managers and policymakers to improve land management, which will contribute to increased agricultural production efficiency and food security in the face of climate change